PENGEMBANGAN MEDIA CD INTERAKTIF PADA MODEL DIKLAT KERJA COMPETENCY BASED TRAINING (CBT) DALAM UPAYA MENINGKATAN KOMPETENSI KEARSIPAN PESERTA DIKLAT BLK SURAKARTA - Nodyawati, Eka; Martono, Trisno; Riani, Asri Laksmi (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
The purpose of this research: 1) develop media valid CD interactive to increase the competency participants training business school and management BLK Surakarta, 2) analyze effectiveness of media CD interactive to increase the competency participants training business school and management BLK Surakarta. This research used the research and development (R&D). Validation internal development media CD interactive on the model training work Competency Based Training (CBT) involving media experts, the people of material and practitioners. Analysis of the data used was descriptive analysis qualitative and the quantitative analysis use test one way anova. Value validation products obtained from media experts of 84,99 %, the people of matter of 84.25 % and practitioners of 85,51 % shows the average validation products of 84,54 % which means had qualified for very good. In the field there are significant differences average score posttest between the experiment to the control group with the significance (sig.) as much as 0.00 <  α (0.05). Value obtained from validation and the the field show that the product of development media CD interactive being used as a medium learning and effective to increase the competency participants training for BLK Surakarta.